Longitudinal analysis of outpatient physician visits in the oldest old: results of the AgeQualiDe prospective cohort study - Hajek, André; Weyerer, Siegfried (The journal of nutrition, health & aging, 2018)
The aim of this study was to identify determinants of outpatient health care utilization among the oldest old in Germany longitudinally.
Gesehen am 13.10.2020